2021
DOI: 10.1021/acs.analchem.1c00301
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Structural Changes of Dyes Lead to Distinctly Different Fluorescent Behaviors in Cellular Context: The Role of G-Quadruplex DNA Interaction Using Coumarin–Quinazolinone Conjugates as a Case Study

Abstract: Fluorogenic organic materials have gained tremendous attention due to their unique properties. However, only a few of them are suitable for bioimaging. Their different behaviors in organic and cellular environments hinder their application in bioimaging. Thus understanding the photoluminescent behaviors of organic materials in a cellular context is particularly important for their rational design. Herein, we describe two coumarin-quinazolinone conjugates: CQ and MeCQ. The high structure similarity makes them p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…CTQ, as expected, exhibited selectivity toward G4 and an overall preference to parallel and hybrid topology G4s like its precursor CQ. 12 The results can also be confirmed with nakedeye observation (Figure 4C). After a Job's plot for assuring the binding ratio, we checked the data availability, fitted it with a proper equation and the derived energy changes (Figures S24−S25 and Table S5).…”
Section: Global Experimental Materials and Instrumentationsupporting
confidence: 79%
“…CTQ, as expected, exhibited selectivity toward G4 and an overall preference to parallel and hybrid topology G4s like its precursor CQ. 12 The results can also be confirmed with nakedeye observation (Figure 4C). After a Job's plot for assuring the binding ratio, we checked the data availability, fitted it with a proper equation and the derived energy changes (Figures S24−S25 and Table S5).…”
Section: Global Experimental Materials and Instrumentationsupporting
confidence: 79%
“…Moreover, the bright fluorescence signal in HepG2 cells is still able to be observed after staining with 4b and 4c for 8 h (Figure S18), suggesting the compounds are stable in cell. It was reported that the lipophilic cationic dyes are easily accumulated in mitochondria, [58] so we speculate the fluorescence signal in cytoplasm maybe come from the mitochondria. Figure 8 shows the CLSM images by the Mito-Tracker dye and the compound co-staining, and it is found that their positions are highly overlapped.…”
Section: Confocal Fluorescence Imagingmentioning
confidence: 80%
“…quadruplex DNA after interacting with the compounds (Figure S15). According to the characteristic of CD signal, bcl-2 [57] and HRCC [58] exhibit a mixed-type conformation, while c-kit 2 [59] and c-myc [60] are a parallel one. HTG shows a hybrid and antiparallel Gquadruplex in buffer containing 100 mM K + and 100 mM Na + , respectively.…”
Section: Interactions Of the Compounds With Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…To address these challenges related to mtDNA G4s, we reasoned that accurate tracking of such noncanonical structures using small-molecule fluorescent probes in live cells would be a practical and effective first step. To date, several fluorescent probes have been developed to selectively stain mtDNA G4s in cells; however, the fluorescence of the probes is distributed diffusely and uniformly over the mitochondria. This staining pattern surprisingly differs from the punctate distribution of mtDNA indicated by the commercial dye PicoGreen or by fluorescent protein-tagged mitochondrial transcription factor A (TFAM). Obviously, a more applicable mtDNA G4-specific fluorescent probe is required to understand the biological roles of mtDNA in greater detail.…”
Section: Introductionmentioning
confidence: 99%